Biosorption of Hexavalent Chromium (Cr(VI)) from contaminated water using charred tea waste (BIBECHANA, 2023)
The goal of this study is to develop charred tea waste (CTW) via chemical process for the removal of Cr(VI) from contaminated water. Batch adsorption experiments were conducted as a function of pH, initial concentration, contact time and adsorbent dosage. Characterization of the adsorbent was analyzed by FT-IR and XRD. Maximum adsorption capacity (qm) of the CTW was found to be 85.32 mg/g at optimum pH 2 in 120 minutes. The adsorption on CTW was well fitted to the Langmuir isotherm and the kinetic data is consistent with the pseudo-second order kinetic model. The findings suggest that CTW could be an efficient and promising adsorbent for the removing Cr(VI) from aqueous solution.